Nexus Between Remittance and Economic Growth: Case of Top Remittance Recipient Countries - Chhetri, Sirjana (Economic Review of Nepal, 2023)
This paper aims to explore the nexus between remittance and economic growth in the top twenty remittance-recipient countries defined in terms of remittances to GDP ratio by using the panel cointegration approach. Panel data from 2009 to 2022 have been used for the Pedroni and Kao Cointegration test and panel ARDL approach to cointegration. Results showed that while there exists a long-run equilibrium relationship among the variables with a very high degree of adjustment in disequilibrium, remittance flows appear to affect economic growth adversely in the long run. Trade openness and gross fixed capital formation positively affected economic growth while inflation reduced growth in the long run. These results imply that the top remittance-recipient countries need to use remittances productively while addressing their structural problems hindering economic growth including high dependence on external sources and imports, low financial access, weak rule of law, and weak quality of institutions.